Deskripsi Pemahaman Konseptual dan Prosedural pada Materi Persamaan Garis Lurus ditinjau dari Kecerdasan Logis Matematis Siswa - Tuti Alawiya; Muhammad Dinar; Asdar (Issues in Mathematics Education (IMED), 2022)
This study aims to determine the description of conceptual and procedural understanding on the material of straight-line equations when viewed from the logical mathematical intelligence of students. To fulfill this objective, a descriptive qualitative research was conducted. The subjects of this study consisted of 3 people, one each from high, medium, and low mathematical logical intelligence students in class IX SMP. The instruments in this study were logical mathematical intelligence tests, conceptual and procedural understanding tests and interview guidelines. The material used is straight line equation material. The results showed that on conceptual understanding, subjects with high mathematical logical intelligence were able to understand 3 indicators, moderate mathematical logical intelligence 4 indicators, and low mathematical logical intelligence 1 indicator. In procedural understanding, the three subjects did not understand each indicator well